Productivity, demand and the home market effect (2018)
The nature of causality between international trade and industrialization remains ambiguous. We consider a model of international trade that features the home market effect—where there are differences in income and productivity between sectors and between countries—to identify additional channels by which to determine the effects of international trade on industrialization. The introduction of non-homothetic preferences and differences in productivity can aid in interpreting of some apparent paradoxes within international trade, such as the commercial relations between more populated countries as China and India and large economies in term of their GDP as the U.S. Population size, demand composition, and productivity levels constitute the three main channels by which to determine the effects of international trade. Interactions among these channels define the results obtained, especially in terms of the countries’ industrialization levels. Additionally, we find that welfare levels under trade are always higher than those under autarky.